Long Non-Coding RNA 554 Promotes Cardiac Fibrosis via TGF-β1 Pathway in Mice Following Myocardial Infarction - Luo, Bihui; He, Zhiyu; Huang, Shijun; Wang, Jinping; Han, Dunzheng; Xue, Hao; Liu, Peiying; Zeng, Xiaojun; Lu, Dongfeng (Frontiers in Pharmacology, 2020)
Rationale: Cardiac fibrosis is observed in nearly every form of myocardial disease. Long non-coding RNAs (lncRNAs) have been shown to play an important role in cardiac fibrosis, but the detailed molecular mechanism remains unknown. Object: We aimed at characterizing lncRNA 554 expression in murine cardiac fibroblasts (CFs) after myocardial infarction (MI) to identify CF-enriched lncRNA and investigate its function and contribution to cardiac fibrosis and function. Methods and Results: In this study, we identified lncRNA NONMMUT022554 (lncRNA 554) as a regulator of MI-induced cardiac fibrosis. We found that lncRNA 554 was significantly up-regulated in the mouse hearts following MI. Further study showed that lncRNA 554 was predominantly expressed in cardiac fibroblasts, indicating a potential role of lncRNA 554 in cardiac fibrosis. In vitro knockdown of lncRNA 554 by siRNA suppressed fibroblasts migration and expression of extracellular matrix (ECM); while overexpression of lncRNA 554 promoted expression of ECM genes. Consistently, lentivirus mediated in vivo knockdown of lncRNA 554 could inhibit cardiac fibrosis and improve cardiac function in mouse model of MI. More importantly, TGF-β1 inhibitor (TEW-7197) could reverse the pro-fibrotic function of lncRNA 554 in CFs. This suggests that the effects of lncRNA 554 on cardiac fibrosis is TGF-β1 dependent. Conclusion: Collectively, our study illustrated the role of lncRNA 554 in cardiac fibrosis, suggested that lncRNA 554 might be a novel target for cardiac fibrosis.